Psychological stress and associated factors among municipal solid waste collectors in Hanoi, Vietnam: A cross-sectional study. - Quynh Thuy Nguyen; Bang Van Nguyen; Ha Thi Thu Do; Bich Ngoc Nguyen; Van Thanh Nguyen; Son Thai Vu; Thuy Thi Thu Tran (PLoS ONE)
Introduction In low and middle-income countries, the manually operated municipal waste collection system prominently depended on the performance of waste collectors (WC). Most of the literature has focused on the impact of waste collection tasks on WCs' physical health, while little was known about the psychological effects of work-related stress. This study aimed to examine the prevalence of psychological stress and related factors among waste collectors in Hanoi, Vietnam. Methods A cross-sectional survey was conducted among 802 WCs in 2017. The questionnaire included the 7-item Stress component of the 21-item Depression, Anxiety and Stress Scale, and questions on demographics and work conditions. Descriptive and multivariate logistics regression analyses were conducted to examine the factors related to psychological stress among WCs. Results Results showed that 13.4% of WCs reported stress symptoms; among them, 3.3% of WCs experienced severe stress. Factors related to lower odds of self-reported psychological stress included self-perceived frequent exposure to high and low temperatures in the working environment (OR = 0.51 and 0.52, respectively). Factors associated with the increased likelihood of symptoms included frequent exposure to hot/flammable objects (OR = 2.41), working a night shift in the last three months (OR = 1.82), education lever lower than high school (OR = 1.82), and having an insufficient monthly income (OR = 1.99). Conclusion The high percentage of workers with severe stress implies the need for mental health prevention and treatment for WCs who participated in this study.